The Effect of Using Sway Media on Interest and Learning Outcomes Learners in the Learning of History Of Islam at MTs Arifah Gowa - Ahmad Suryadi (Proceeding International Conference on Religion, Science and Education, 2023)
This type of research is an ex post facto approachmethodology namely quantitative and scientific approach in the form of psychology, Meanwhile Respondents in this study amounted to 103 people using the method Non-Probability Sampling. The research instruments used were questionnaires and Documentation format analyzed using descriptive and inferential statistics by doing the F test. Based on the results of descriptive statistical analysis, the results of Media research were obtained Sway is in the medium category, namely 70% with an average value of 46.85, whichcaused by the Media Sway indicator factor. The results of the descriptive statistical analysis of interestthe learning of students at MTs Arifah Gowa is locatedin the medium category, namely 68% with an average value of 43.39 which is caused byindicator factor of interest in learning. And the results of descriptive statistical analysis of learning outcomes students at MTs Arifah Gowa are inmedium category, namely 67% with an average value of 82.17 which is caused by factors learning outcome indicators. Based on the processing results of inferential statistical analysis of media variables Sway (X) to the learning outcomes (Y2) of students at MTs Arifah Gowa obtained the results of the analysis of tcount = 2.202 while the value of ttable = 1.66means that the tcount value is greater than the ttable value (tcount > ttable = 2,202 > 1.66). Thenobtained Fcount = 1.445 and Ftable value 3.09 and p-value/Sig. = 0.000 < 0.05or Ho is rejected and Ha is accepted or the significance is smaller than the error leveldetermined. Thus, there is an influence of Media Sway on learning outcomes students at MTs Arifah Gowa.